2002
DOI: 10.1091/mbc.e01-11-0107
|View full text |Cite
|
Sign up to set email alerts
|

Downstream E-Box–mediated Regulation of the Human Telomerase Reverse Transcriptase (hTERT) Gene Transcription: Evidence for an Endogenous Mechanism of Transcriptional Repression

Abstract: Regulation of the hTERT gene encoding the telomerase catalytic subunit plays an important role in human cell senescence, immortalization, and carcinogenesis. By examining the activity of various deleted or mutated hTERT promoter fragments, we show that an E-box element downstream of the transcription initiation site is critical to differential hTERT transcription between the telomerase/hTERT-positive renal cell carcinoma cell line (RCC23) and its telomerase/hTERTnegative counterpart containing a transferred, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
101
2
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 96 publications
(110 citation statements)
references
References 43 publications
6
101
2
1
Order By: Relevance
“…Such transcription factors, for example Mad1 and MT-box-binding factor, have been reported to function as repressors of the hTERT promoter that act when cancer cell differentiation is induced by antagonizing the transcriptional activation ability of c-Myc (Tzukerman et al, 2000;Xu et al, 2001;Horikawa et al, 2002). Although our results showed that TAK1 represses the hTERT promoter activity in an E-box-independent manner, we cannot exclude the possibility that TAK1 represses the hTERT promoter even in an E-box-dependent manner.…”
Section: Discussioncontrasting
confidence: 62%
“…Such transcription factors, for example Mad1 and MT-box-binding factor, have been reported to function as repressors of the hTERT promoter that act when cancer cell differentiation is induced by antagonizing the transcriptional activation ability of c-Myc (Tzukerman et al, 2000;Xu et al, 2001;Horikawa et al, 2002). Although our results showed that TAK1 represses the hTERT promoter activity in an E-box-independent manner, we cannot exclude the possibility that TAK1 represses the hTERT promoter even in an E-box-dependent manner.…”
Section: Discussioncontrasting
confidence: 62%
“…These studies show that the human and mouse TERT genes are regulated by inducible transcription factors including c-Myc, Sp1 and NFkB (Horikawa et al, 1999;Wick et al, 1999;Wu et al, 1999;Kyo et al, 2000;Yin et al, 2000;Oh et al, 2000;Tzukerman et al, 2000;Poole et al, 2001). However, these studies were not carried out with a complete hTERT gene including all putative regulatory elements and introns.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptional activation of the hTERT gene is a critical, initial rate-limiting step in telomerase activation in human cancers. The hTERT gene promoter provides a platform with a number of binding sites for transcriptional regulation, including two typical E-boxes and several GCboxes for the transcription factors c-myc/Max and Sp1, respectively [29][30][31]. Expression of c-myc rapidly induces hTERT gene transcription [32], with the binding of c-myc to the E-box being coupled to cell proliferation and that is disengaged by Mad1 during differentiation [33].…”
Section: Telomeres and Telomerasementioning
confidence: 99%